Analisis Efektivitas Proses Evakuasi Kebakaran di Kapal MT. Elisabet Satu - Ambarsari, Evrilia; Suprapti, Fitri; Nindita, Kirtyana; Kumara, Rahindra Bayu (PPPM Polimarin, 2025)
Fire on a tanker can cause financial, human, and environmental losses if it is not handled effectively. This research aimed to find out the actions of the captain when conducting an evacuation, to determine the factors inhibiting the evacuation process, and to analyze the effectiveness of the fire evacuation process on MT. Elisabet Satu. This research used qualitative method combined with the root cause analysis (RCA) and fishbone diagram. This research used observation, interviews, documentation, and literature studies to collect the data. The object of this research was the fire evacuation process on MT. Elisabet Satu. The results of this research indicated that the captain had followed the evacuation procedures when conducting the fire evacuation on MT. Elisabet Satu. In addition, there were five main factors that inhibited the evacuation process when a fire occured on MT. Elisabet Satu. However, even though the evacuation procedures had been carried out properly, the evacuation process could not be fully declared effective based on the Risk-Based Evaluation in ISM Code.